Respostas

2014-03-05T12:52:02-03:00
A(4,3)                                        
B(2, -1)

F(x)= ax+b
3= a4+b
4a+b=3

F(x)= ax+b
-1=a2+b
2a+b= -1

multiplica por -1 --> {4a+b=3 --> -4a-b=- 3
                             {2a+b=-1 --> 2a+b=-1
                                              ------------------
                                                -2a= - 4
                                                  a= - 4/- 2
                                                  a= 2

2a+b= - 1
(2 . 2) + b = - 1
4 + b = - 1
b = - 1 - 4
b = - 5


F(x) = ax + b
y = ax + b
y = 2x + (-5) ----> Essa é a função